Nurse‐to‐nurse shift handoffs on medical–surgical units: A process within the flow of nursing care. Issue 5 (25th January 2018) - Ernst, Katherine M; McComb, Sara A; Ley, Cathaleen
Abstract : Aims and objectives: To qualitatively investigate the medical–surgical nurse shift handoff as a process within the workflow of the exchanging nurses. Specifically, this study sought to identify the ideal handoff, ways the handoff deviated from ideal, and subsequent effect on nursing care. Background: The functions as well as information content of the handoff have been studied. However, typical studies look at the handoff as an isolated activity utilising nurse perceptions as the primary measure of quality. Design: Semi‐structured focus groups were conducted to discuss nurses' perspectives on ideal handoffs, ways handoffs deviate from the ideal including frequent and significant deviations and the effects on subsequent care. Methods: Twenty‐one medical–surgical nurses participated in one of five audio‐taped focus group sessions. Three sessions were conducted at hospital A; two sessions at unaffiliated hospital B. The general inductive approach was used to analyse verbatim transcripts. Transcript segments relevant for answering the research questions were coded as ideal or not ideal. Conceptual themes were then developed. Result: Two major themes were identified: teams/teamwork and constructing and communicating a shared understanding of the patients' conditions. The importance of nurse preparatory activities was revealed including the incoming nurses reading patients' health records and outgoing nurses rounding on patients. The impact of shared expectations was identified across the team, where teams include, in addition to the two nurses, the electronic health record, other hospital staff and patients/families with a bedside handoff. New potential nurse‐centred process and outcome measures were proposed. Conclusions: Evaluating handoffs by their effect on the nursing performance both during and after the handoff offers a new framework to objectively assess handoff effectiveness. Relevance to clinical practice: The handoff is a process which may significantly affect the incoming nurse's transition into and administration of nursing care.